A Review on the Modeling of the Clinching Process Chain - Part III: Operational Phase - Schramm, Britta; Harzheim, Sven; Weiß, Deborah; Joy, Tintu David; Hofmann, Martin; Mergheim, Julia; Wallmersperger, Thomas (Journal of Advanced Joining Processes, 2022)
The mechanical joining technique clinching is often used in order to realize components of different complexity with numerous connection points. For the holistic prognosis of the joinability and the life cycle of an assembly, numerical modeling of the complete joining process chain is essential considering (i) the design phase, (ii) the joining process itself and (iii) the operational phase. Such a holistic modeling approach enables the comprehension of the complex cause-and-effect relationships in mechanical joining of different materials (e.g. aluminum, steel and fiber-composite). Besides plasticity and damage processes during the clinching process, corrosive phenomena and crack propagation behavior have to be taken into account for the prognosis of the load-bearing capacity and of the lifetime. This paper is the third part (part III) of a review series summarizing the current state of research on modeling and simulation of clinching. The focus of part I is on the joining process chain and its challenges as well as on the design phase. The joining process itself, i.e. the process simulation of the clinching process as well as damage phenomena, is subject of part II. Within the scope of the current paper (part III) of our review series are the influences of the operating phase. Thereby, the effects of corrosion and of fatigue crack growth as well as corresponding modeling approaches are considered.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Clinching; Corrosion modeling; Crack growth simulation; Mechanical joining; Process chain